Automatic refinement and efficient solver for non linear dynamic structural problems - Biotteau, Ewen; Gravouil, Anthony; Lubrecht, Antonius; Combescure, Alain (European Journal of Computational Mechanics, 2010)
This paper presents an adaptive strategy dedicated to non-linear transient dynamic problems. The spatial mesh is optimized to ensure the accuracy of the solution. Beginning from a coarse mesh, an error indicator is used to estimate the discretization error and new elements are created where the prescribed accuracy is not reached. A localized multigrid solver is used and the strategy is applied recursively until the local mesh size ensures that the discretization error is less than the prescribed accuracy. The spatial mesh is recreated at each time step.